Network Pharmacology and Validation Experiments Reveal Cryptotanshinone Inhibits Acute Myeloid Leukemia Progression by Activating Endoplasmic Reticulum Stress - Wei, Jie; Yao, Xiang You; Huang, Yan; Nai, Guan-ye; Liu, Rong-rong (Current Medicinal Chemistry, 2025)
<span class=
Keywords: endoplasmic reticulum stress